Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1002/etc.5620201231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bioassays versus contaminant concentrations in explaining the macroinvertebrate community structure in the Rhine‐Meuse delta, The Netherlands

Abstract: It is often assumed that bioassays are better descriptors of sediment toxicity than toxicant concentrations and that ecological factors are more important than toxicants in structuring macroinvertebrate communities. In the period 1992 to 1995, data were collected in the enclosed Rhine-Meuse delta, The Netherlands, on macroinvertebrates, sediment toxicity, sediment contaminant concentrations, and ecological factors. The effect of various groups of pollutants (polycyclic aromatic hydrocarbons, trace metals, oil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…Differences in the dominance of phytoplankton and invertebrate populations between microcosm types may have been caused directly by differences in sediment quality, or indirectly by differences in macrophyte biomass. Several field studies have revealed that both sediment-bound toxicants (Peeters et al 1999;Reinhold-Dudok van Heel and Den Besten 1999; Tables 4 and 5 Ecotoxicology (2006) Peeters et al 2001) and beds of aquatic vascular plants (LaLonde and Downing 1992;Brock and Van der Velde 1996;Scheffer 1998) have a significant effect on invertebrate communities.…”
Section: Influence Of Sediment Qualitymentioning
confidence: 99%
“…Differences in the dominance of phytoplankton and invertebrate populations between microcosm types may have been caused directly by differences in sediment quality, or indirectly by differences in macrophyte biomass. Several field studies have revealed that both sediment-bound toxicants (Peeters et al 1999;Reinhold-Dudok van Heel and Den Besten 1999; Tables 4 and 5 Ecotoxicology (2006) Peeters et al 2001) and beds of aquatic vascular plants (LaLonde and Downing 1992;Brock and Van der Velde 1996;Scheffer 1998) have a significant effect on invertebrate communities.…”
Section: Influence Of Sediment Qualitymentioning
confidence: 99%
“…Furthermore, mixtures of pollutants make it difficult to ascribe observed effects to one or more substances. Recently, a specific multivariate statistical approach has been used to quantify the impact of pollutants on benthic communities in relation to the effects of other factors [13–15]. This approach, the variance partitioning method, can be applied to assess the contribution of pollutants relative to the effect of other variables, for example, water, sediment, and other habitat characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Since baetids can rapidly colonize these environments (Richards and Minshall, 1988), they may have been able to avoid exposure to the fine sediment that likely contained the heavy metals and PAHs. The ability of physical habitat or environmental factors to override or confound the influence of toxicants on benthic communities has been noted by others as well (Peeters et al, 2001; Carew et al, 2007). Alternatively, some species of the genus baetidae are tolerant of heavy metals (Aoki et al, 1989; Cain et al, 2004) which may have allowed them to proliferate at LBC 4, even in the presence of high toxicant concentrations.…”
Section: Discussionmentioning
confidence: 83%